2005
DOI: 10.1091/mbc.e05-08-0778
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Cyclooxygenase-2 in Response to Proteasome Inhibitors Involves Reactive Oxygen Species-mediated Signaling Pathway and Recruitment of CCAAT/Enhancer-binding Protein δ and CREB-binding Protein

Abstract: Inhibition of ubiquitin-proteasome pathway has been shown to be a promising strategy for the treatment of inflammation and cancer. Here, we show that proteasome inhibitors MG132, PSI-1, and lactacystin induce COX-2 expression via enhancing gene transcription rather than preventing protein degradation in the human alveolar NCI-H292 and A549, and gastric AGS epithelial cells. NF-IL6 and CRE, but not NF-κB elements on the COX-2 promoter were involved in the gene transcription event. The binding of CCAAT/enhancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…Cells were then rapidly washed with PBS and lysed with ice-cold lysis buffer (50 mM Tris-HCl (pH 7.4), 1 mM EGTA, 1 mM NaF, 150 mM NaCl, 1 mM PMSF, 5 g/ml leupeptin, 20 g/ml aprotinin, 1 mM Na 3 VO 4 , 10 mM ␤-glycerophosphate, 5 mM Na 4 P 2 O 7 , and 1% Triton X-100), as previously described (16).…”
Section: Preparation Of Total Cell Lysates and Nuclear Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were then rapidly washed with PBS and lysed with ice-cold lysis buffer (50 mM Tris-HCl (pH 7.4), 1 mM EGTA, 1 mM NaF, 150 mM NaCl, 1 mM PMSF, 5 g/ml leupeptin, 20 g/ml aprotinin, 1 mM Na 3 VO 4 , 10 mM ␤-glycerophosphate, 5 mM Na 4 P 2 O 7 , and 1% Triton X-100), as previously described (16).…”
Section: Preparation Of Total Cell Lysates and Nuclear Extractsmentioning
confidence: 99%
“…Binding of transcription factors to the DR5 intron was assayed as previously described (16). The nuclear extract (400 g) was precleared at room temperature for 1 h with 20 l of the 4% streptavidin-coated beads (SigmaAldrich) mixed with 50% slurry to reduce nonspecific binding.…”
Section: Dna Affinity Protein-binding Assay (Dapa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that, during inflammation, C/EBPδ is recruited to the promoter region of cyclooxygenase-2, although its expression levels remained constant (19). Currently, to the best of our knowledge, no conclusive study of the expression levels of C/EBPδ in GC cells has been performed.…”
Section: Discussionmentioning
confidence: 95%
“…NF-κB is a vital regulator of a number of proinflammatory genes, including iNOS, COX-2, TNF-α, IL-1β, and IL-6, in LPS-induced inflammation. [21][22][23] Generally, the inactive complex of NF-κB with IκB exists in the cytoplasm. IκB is rapidly phosphorylated in response to proinflammatory stimuli, leading to dissociation of the complex.…”
mentioning
confidence: 99%